A novel dimeric proanthocyanidin 3-O-glucoside from Quercus ilex L. (Fagaceae) - Karioti, A.; Bilia, A. R.; Skaltsa, H. (PLANTA MEDICA, 2007)
ity at room temperature in order to deactivate any enzymes and avoid polymerizations and oxidations. Final extraction was carried out using MeOH and MeOH/H2O 8/2. A fast fractionation of the residue was done using VLC over silica gel followed by repeated cc over Sephadex LH-60 and Sephadex LH-20. Fractionations were monitored with HPLC-DAD-MS. The structures of the isolated compounds were established by means of 1D & 2D NMR.
Keywords: Circular dichroism; Fagaceae; Oak-leaves; Proanthocyanidin glycosides; Quercus ilex; ROESY